A Levantine Mansion: Buca Guidance Centre for Disabled Students - Emre Ergül; Beste Demircan (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The aim of this study is to understand what was changed in a Levantine mansion in the Buca district of Izmir, from its construction date to now. Since the construction date is 1876, the study is scoped into a 150 years period in time. The data collection method includes photographic documentation and laser measurements. The evaluation method is comparative analysis to relate the common properties of Levantine houses with the plan typology and the traces in the building. A short periodization and descriptions of each space have been made. The mansion had not experienced radical changes, even if there were handovers in the property ownership. However, it can be analysed by considering small differences. In conclusion, the building is periodized in three-time slices as the 1. Period in the years between 1876 – 1890 / 1895, the 2. Period between 1895 – 1960's and the 3. Period from the 1960s to now.